Peculiarities of layers of active carbon microparticles with grafted PVC amine derivatives on PVC substrate as sorbents of benzene and water vapour - M. P. Shabanov; A. Yu. Tsivadze; A. Ya. Fridman; E. M. Morozova (Carbon: Science and Technology, 2019)
The limit sorption capacity of active carbon layers with grafted ethanolamine, sodium or potassium glycinate derivatives of PVC with different fractions of components formed on a PVC film was measured under sorption of saturated benzene and water vapor. Sorbents are considered as systems with two porous phases chemically bounded at the interface. The compound to be sorbed is absorbed from the outside by the polymer with the formation of molecular complexes with PVC derivatives and through it passes into carbon to establish the equilibrium state of the distribution under conditions of maximum saturation of the polymer. It is shown that the amount of benzene and water in carbon is less than its capacity. It depends on the nature of the radicals in the PVC derivatives.